(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The goal of this study is to find out how much consumers are aware of the Government Incentives for Electric Vehicles. For this purpose, primary data has been collected through the interview methods. Simple random sampling method has been used for collection of the data. Sample size for the present study is 157. The present study reported that there is a significant level of consumers’ awareness about the government incentives toward electric vehicle. It is found that males are more aware than females about Government providing income tax deduction on purchase of EVs. It is concluded that males agree more than females on no requirement of licence for youth (16-18 yrs.) to drive an EV (two wheeler). It can be concluded that males are found more aware than females about the subsidy provided by the government on the purchase of an EV. It can be concluded that males are found more aware than females regarding EVs getting a concessional treatment at toll gates. Males are slightly highly aware about green number plates, EVs preferred parking and free admission in crowded zones. Respondents having bachelor degree are slightly more aware about government incentives toward electric vehicle. Semi-urban residents are slightly more aware about government incentives towards electric vehicle.